Outsourcing (Field Checker) Competency Assessment and Improvement Strategy as Substitution for Oil & Gas Company’s Field Operator (The Indonesian Journal of Business Administration, 2021)
PT.XYZ, an Oil and gas company, suffered from oil prices that fell in 2016. To maintain Company sustainability, the strategies is reducing operating cost, such as changing the organizational structure, reducing the number of employees, for job’s position that replaced by outsourcing.FOD, with more than 70% of its employees being Field Operators, lose 30% of its Field Operators. From 2016 to 2020, the Field Operator will decrease 30%, and in the next year there will be 20% of Field Operators retiring. For one year now, FOD has used an outsourcing / business partner to fill the Field Operator position, with the name Field Checker. Over time, the competence of Field Checker did not develop as expected. decreased production and minor accidents occurred.Competency assessment of Field Checker is carried out through a questionnaire. The results of the questionnaire show that 68% of all Field Checkers have not shown the desired competency, Program development will be carried out on Field Checkers is a strategic systems model, using of competency-based rewards and recognition in Field Checker remuneration, evaluation per semester, and the division of groups using the normal distribution method.Keywords: Oil and Gas Company, sustainability, outsourcing, competency, assessment, development.